The Contemporary Career Theory as a Lens for Understanding the Internationalization of Business Schools Students - Marcello Romani-Dias; Seimor Walchhutter; Caio Sousa da Silva; Luis Henrique Rigato Vasconcellos (SAGE Open)
This article starts from gaps found in the literature on international students. The literature points out that we need studies on the subject that: bring different student profiles to explain their internationalization; explain, beyond mere description, the factors that motivate students to internationalize their studies and careers; and that they are conducted based on a guiding theory. In order to identify the main motivators of students for the internationalization of their careers, and to bring a theoretical view pointed out by the international education literature as necessary, we conducted a qualitative research by triangulating information from the literature on student internationalization, from the precepts of contemporary career theory, and interviews with students from an internationally accredited business school, to argue that the internationalization of these students is strongly stimulated by the peculiarities of the contemporary career they want for their lives. We used the content analysis technique as the main method of data analysis, with the support of the systematic coding technique to define our categories of analysis. Through this methodological design, we identified three main precepts of the theory that help explain student internationalization: (i) desire to expand their networks and broaden their cultural knowledge; (ii) search for greater autonomy of decision and professional alternatives; (iii) development of their soft skills and ability to solve complex problems. With these results we make contributions to the research topic, for students and for business schools.